Multimodal response characteristics of convective liquid metal sensitive layers in flexible pressure sensor - Qing Wang; Zhou Zhou; Jizhang He; Liang Zhuo; Chenlin Zhu; Wenjie Qian; Wei Shi; Daoheng Sun (Microsystems & Nanoengineering)
Abstract The development of electronic skin, soft robots, and smart wearables has significantly driven advances in flexible pressure sensing technology. However, traditional multilayer solid-structure flexible pressure sensors encounter challenges at temperatures between 100 °C and 150 °C due to high-temperature modal distortion. Changes in the conductivity of the sensor’s conductive components interfere with accurate pressure measurement. In this research, a flexible pressure sensor with a convective liquid metal sensitive layer is proposed. The sensor uses a cyclic self-cooling mechanism to lower the temperature of its conductive components, reducing the impact of external high temperatures on the pressure measurement accuracy. At a 2.8 W thermal load, the flexible sensor, with liquid metal circulating at 2.0 mL/min, exhibits a sensitivity of 0.11 kPa⁻¹ within the pressure range from 0 to 12.5 kPa, and its maximum measurable pressure is 30 kPa. In addition, the resistance of the sensor is 18.5 mΩ less than that of a stationary liquid metal sensor, representing a 38.1% reduction. The sensor proposed in this research introduces a novel strategy for pressure measurement in high-temperature applications, extending the application scope to aircraft, special robots, and hydraulic oil circuits.